Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4172/2155-6113.1000453
|View full text |Cite
|
Sign up to set email alerts
|

HIV Associated Chronic Obstructive Pulmonary Disease in Nigeria

Abstract: Objective To determine the prevalence and risk factors for chronic obstructive pulmonary disease (COPD) among HIV-infected adults in Nigeria. Design Cross-sectional study. Methods HIV-infected adults aged ≥ 30 years with no acute ailments accessing care at the antiretroviral therapy clinic of Jos University Teaching Hospital were enrolled consecutively. Participants were interviewed to obtain pertinent demographic and clinical information, including exposure to risk factors for COPD. Post-bronchodilator sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 37 publications
5
30
4
1
Order By: Relevance
“…We did not find any correlation between ART exposure and COPD, nor between hepatitis and COPD, contrary to some previous studies using smaller populations [10,12,14,32]. Some previous studies also discussed an association between pneumocystis pneumonia or tuberculosis pneumonia with COPD [10, 19]. Our study did not find any association with these pathologies, but their low frequency in our population did not allow for any meaningful conclusions on this point (S1 Table).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find any correlation between ART exposure and COPD, nor between hepatitis and COPD, contrary to some previous studies using smaller populations [10,12,14,32]. Some previous studies also discussed an association between pneumocystis pneumonia or tuberculosis pneumonia with COPD [10, 19]. Our study did not find any association with these pathologies, but their low frequency in our population did not allow for any meaningful conclusions on this point (S1 Table).…”
Section: Discussioncontrasting
confidence: 99%
“…04) [11]. Since the publication of this result, 5 high quality studies using spirometric criteria have found COPD rates between 6% and 21% in groups of 65 to 400 HIV outpatients representative of patients commonly treated in consultation units in the United-States, Spain, Italy and Nigeria [12,13,16,19,20]. Differences in prevalence were expected due to dissimilarities of methodology, age, smoking, histories and country-related respiratory exposure usually observed between the countries, but all of these studies confirmed similar high frequency of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarises the characteristics of included studies. 18 studies were from the Americas (Canada, Colombia, and the USA), [57][58][59][60][61][62][63][64][65][66][67][68][69]71,74,76,81,82 six were from Europe (Denmark, France, Italy, Spain, and UK), 70,72,75,76,79,80 four were from Africa (Cameroon, Nigeria, South Africa, and Uganda), 47,56,77,83 and one was from Japan. 77 One multiregional study included all WHO regions.…”
Section: Resultsmentioning
confidence: 99%
“…Their lower prevalence may be explained by a comparatively younger population with a lower smoking prevalence. Conversely, Nigerian investigators measured 15.4% prevalence of COPD among PLWH in urban Nigeria, although no association was found between COPD and tuberculosis[22]. Importantly, viral control was less common in the Nigerian cohort.…”
Section: Discussionmentioning
confidence: 99%